Emotional Attraction on Grabmart Ads “Kasih Selalu Sampai Karena Kasih Sayang Gak Pake Ditunda” - Fitri Norhabiba,; Tatak Setiadi,; Anam Miftakhul Huda,; Danang Tandyonomanu,; Tsuroyya,; Ade Firmannadya, (Technium Social Sciences Journal, 2023)
Advertising is one of the important initiatives in introducing, providing information, selling and building a brand of a product and service. Good advertising can benefit the advertiser/entrepreneur. In the digital age nowadays there are a variety of advertising media that can be found. The method used is qualitative descriptive. This method aims to describe the data obtained by observing the phenomena directly. The object of the research is a grabmart advertisement of an irretrievable love edition that can be accessed on youtube. This research focuses on messages contained in pieces or ad scenes using an emotional approach. In those ads the scenes are shown not far from the family's day-to-day life. Love for your children, for yourself, and also for your loved ones, the excitement of friends can't be delayed either. Marketers or communicators can use emotional appeals in creating creative designs on their ads, especially to show how the characters in those ads get the emotional result or benefit from the brand of goods or services they offer.